Political Bases as the Epicenter of Violence: Cases of Mazowe and Shamva, Zimbabwe. Issue 2 (2nd April 2016) - Dodo, Obediah; Nsenduluka, Everisto; Kasanda, Sichalwe
ABSTRACT: Political bases have been a feature in Zimbabwe's election periods. They have been used as institutions for the perpetuation of terror, pain, fear, and coercion among others. While they are established by formal political movements and sponsored by various stakeholders, they are largely driven and sustained by the youth, who are sometimes abused while in others, they capitalize on the situation to further criminal activities. This discussion looks at the political base concept in the two districts of Mazowe and Shamva postindependence with a view to establish their role, implications on society and development, and identify associated stakeholders. The discussion is extracted from a research that was conducted in pursuit of a doctoral degree on traditional taboos and conflict resolution. The research conducted through a mixed approach, employed formal interviews, focus group discussions, and archival material to gather data from a sample of 135 participants. Participants had been selected through snowball and emergent sampling modes. The study established that the existence of political bases had a serious negative impact on traditional systems, development, and people as there was destruction of property, displacement, injury, and extermination of people's lives, manifestation of diseases, and erosion of some cultural practices.